Management of community water storage structures in Indian villages – a case study on measuring performance - PANDE, V. C.; BHATNAGAR, P. R.; RAO, B. K. (Journal of Soil and Water Conservation, 2021)
Decentralization of rural water services for smooth management and delivery of rural water services, world over, is gaining momentum. The decentralization of water resource management has advantages in terms of efficiency and cost effectiveness in resource use. Yet it is fraught with issues like sustainable water resource management, equity in distribution and resource augmentation for serving larger section of rural society. The present study attempts to address the issues and evolve an indicator to measure the sustainability of community water storage structures. A sustainable community-based water storage structure is defined as one that reliably delivers water, in perpetuity, without physical and financial support from the external agency such as national and/or local governments. It is based on the premise that a functional water storage structure ensures perpetual water delivery to local stakeholder and, in turn, gets paid for operation and maintenance. The finance generated through fee collected for water use from these structures helps in regular maintenance for improving efficiency of the water delivery system. A functional water storage structure would ensure reliable service, through regular fee collection, on sustainable basis and as such, the functionality of water storage structure and its financial autonomy are interlinked. In this study, the developed indicator was applied to data collected from community water storage structures in selected Indian villages and its utility along with the limitations discussed for further refinement.